Impactos da Lei Modelo da UNCITRAL sobre o desenvolvimento do setor de arbitragem - Bertolani, Lilian Elizabeth Menezes (2023)
The present thesis aims to weave a comparative analysis of international practices with the Brazilian arbitration system and its consequences for the development of the international dispute resolution market. The study is justified by the need to understand: a) what are the prevailing international standards on commercial arbitration; b) what is the importance of legislative harmonization for the promotion of the dispute resolution market and for the global economy and how UNCITRAL has contributed and still contributes to this objective; c) how Brazilian law regulates arbitration procedures and what are the differences between Law 9.307/1996 (Brazilian Arbitration Law) and the UNCITRAL Model Law on International Commercial Arbitration; and d) whether the adoption of the text of the Model Law on International Commercial Arbitration is considered a relevant factor for a jurisdiction to gain prominence and market confidence to host international arbitration proceedings. The paper used the deductive method, based on the collection of statistical data, document analysis, and specialized bibliographic content to recognize, in the end, the contribution of the Model Law to less traditional countries in the dispute resolution market that aim to be international arbitration venues and that Brazil, although it has points to be worked on, has most of the characteristics desired by users in this segment